Views and experiences with regard to antibiotic use of hospitalized patients in five European countries: a qualitative descriptive study. (February 2019) - Zanichelli, V.; Monnier, A.A.; Tebano, G.; Stanić, B.M.; Gyssens, I.C.; Pulcini, C.; Vlahović-Palčevski, V.; Schindler, M.; Harbarth, S.; Hulscher, M.; Huttner, B.D.
Abstract: Objectives: To explore inpatients experiences and views with regard to antibiotics in five European hospitals. Methods: Qualitative study where a patient-centred framework was used to explore inpatients' experiences concerning antibiotic treatment. A purposeful sample of inpatients treated with antibiotics in five hospitals participated in interviews (all centres) and focus groups (Switzerland only). Results: A total of 31 interviews (five in Belgium, ten in Croatia, nine in France, five in the Netherlands and two in Switzerland) and three focus groups (in Switzerland, 11 participants) were performed. The median age of participants was 61 years (range 33–86 years). The following main themes emerged: (a) patients trust doctors to take the best decisions for them even though communication concerning different antibiotic-related aspects is often insufficient, (b) patients feel that doctors do not prioritize communication due to time constraints and do not seem to adapt information based on patients' preferences, (c) patients differ in their wish to be informed but overall want to be informed on the main aspects in an understandable way, (d) patients often find reassurance in sharing information about their antibiotic treatment with close family, (e) professionals should explore patients' preferences to be involved or not in shared decision making for antibiotic treatment. Conclusion: Inpatients often doubt their ability to understand medical information and trust their physicians to take the best decisions for them. Tailored strategies that inform hospitalized patients, acknowledging their concerns and preferences, may be useful to promote patient involvement and to improve communication regarding antibiotic use.